“Deiksis” dalam Puisi Perlawanan dari Persantren Nazam Tarekat Karya K.H. Ahmad ar-Rifai Kalisalak Tinjauan Pragmatik - Darsita Suparno (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: This study attempted to describe the use of deixis in Puisi Perlawanan dari Pesantren. Deixis understood as part of a pragmatic study therefore, deixis is one object of the field of study pragmatics. The problems in this study are namely: 1) what types of deixis are there in this poetry; 2) what is the intention of using social deixis. The purposes are going to be achieved by this study are such as: 1) to describe the various types of deixis, 2) to describe the intention of using social deixis. The object of this study are namely: the various types of deixis, intention and relationship of social deixis. The subject of this research is the poem which is written by K.H. Ahmad ar-Rifai Kalisalak that is edited and translated from Jawi to Java by M. Adib Misbachul Islam. The data in this study are namely: words, phrases, sentences, in the form of couplet in which there are different types and intention of using social deixis. There are two data resources, namely: primary data source in the form of peom and secondary data sources related literature. Data collection techniques in this study using documentation. The results of this study indicate that there are 4,864 couplets, which is divided into 24 Tanbih ‘note or warning’. In this article there are three types of deixis. There are 25 deixis place, and there are 11 persona deixis, then there are 10 social deixis. It consists 3 types of titles, 2 types of social deixis positions, and 5 nicknames social deixis.Abstrak: Penelitian ini berupaya untuk menggambarkan pemakaian deiksis dalam Puisi Perlawanan dari Persantren. Deiksis dipahami sebagai bagian dari studi pragmatik, dengan begitu deiksis merupakan objek bidang kajian dari pragmatik. Masalah dalam penelitian ini: 1) jenis-jenis deiksis apa saja yang terdapat di dalam puisi ini ; 2) bagaimanakah maksud dibalik penggunaan deiksis sosial. Tujuan yang hendak dicapai adalah: 1) untuk mendeskripsikan aneka jenis deiksis, 2) mendeskripsikan maksud penggunaan deiksis sosial. Objek yang dikaji adalah jenis, maksud serta hubungan deiksis sosial. Subjek penelitiannya adalah puisi karya K.H. Ahmad ar-Rifai Kalisalak yang sudah disunting dan diterjemahkan oleh M. Adib Misbachul Islam dari aksara Jawi berbahasa Jawa ke dalam bahasa Indonesia. Data dalam penelitian ini adalah kata, frase, kalimat, dalam bentuk bait-bait puisi yang di dalamnya terdapat jenis dan maksud penggunaan deiksis sosial. Sumber data dalam penelitian ini terdiri dari sumber data primer berupa puisi dan sumber data sekunder literature yang terkait. Teknik pengumpulan data dalam penelitian ini dengan menggunakan dokumentasi. Hasil penelitian ini menunjukkan bahwa sebanyak 4.864 bait, yang dibagi dalam 24 tanbih ‘catatan atau peringatan’. Dalam artikel ini dikemukakan hanya ada tiga jenis deiksis yaitu deiksis tempat berjumlah 25, deiksis persona berjumlah 11 dan 10 deiksis sosial, terdapat 3 deiksis sosial jenis gelar, 2 deiksis sosial jenis jabatan, dan terdapat 5 deiksis sosial jenis julukan.Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v3i2.5183